2023
DOI: 10.3897/neobiota.87.100355
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope values and trophic analysis of invasive three-spined stickleback in Upper Lake Constance points to significant piscivory

Abstract: The three-spined stickleback Gasterosteus aculeatus was introduced into Lake Constance in the 1940s and occupied a limited range until late 2012. Since then the species has expanded from a solely littoral habitat in Upper Lake Constance, but now makes seasonal migrations into the pelagic zone. This behavioral change has been accompanied by a drastic increase in stickleback abundance. In order to integrate information about feeding of sticklebacks in Upper Lake Constance over two consecutive years, stomach cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In ULC in the years after the invasion in 2012, similar patterns were observed when sticklebacks began to migrate to the spawning grounds of whitefish (Gugele et al, 2020). Lake Constance sticklebacks are routinely piscivorous (Gugele et al, 2023) and target whitefish larvae and eggs during and shortly after that species' spawning period (Baer et al 2021). In the present study, remains of fish eggs and larvae in the guts of stickleback were found in all seasons except autumn, but they were most abundant in spring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ULC in the years after the invasion in 2012, similar patterns were observed when sticklebacks began to migrate to the spawning grounds of whitefish (Gugele et al, 2020). Lake Constance sticklebacks are routinely piscivorous (Gugele et al, 2023) and target whitefish larvae and eggs during and shortly after that species' spawning period (Baer et al 2021). In the present study, remains of fish eggs and larvae in the guts of stickleback were found in all seasons except autumn, but they were most abundant in spring.…”
Section: Discussionmentioning
confidence: 99%
“…The full extent of the ecological impact of this pelagic invasion is yet to be evaluated, but direct effects are apparent on the pelagic whitefish Coregonus wartmanni (Bloch 1784), once the dominant keystone pelagic fish species and the main target of local fisheries (Baer et al, 2017). These impacts include interspecific competition for food leading to reduced whitefish growth and survival, and predation by sticklebacks on whitefish larvae and probably eggs, hampering recruitment (Baer et al, 2021; DeWeber et al, 2022; Gugele et al, 2023; Roch et al, 2018; Ros et al, 2019; Rösch et al, 2018). These observations coincide with a sharp decline in whitefish fishery yield, from around 300–600 mt (metric tons) before stickleback invasion to less than 22 mt in 2022 (http://www.ibkf.org).…”
Section: Introductionmentioning
confidence: 99%